A combination of self-disturbances and psychotic-like experiences. A cluster analysis study on a non-clinical sample in Poland. (March 2019) - Gawęda, Łukasz; Pionke, Renata; Arciszewska, Aleksandra; Prochwicz, Katarzyna; Frydecka, Dorota; Misiak, Błażej; Cechnicki, Andrzej; Cicero, David C.; Nelson, Barnaby
Highlights: A cluster analysis of a combination of PLEs and self-disturbances (SD) was performed on large non-clinical sample. Cluster analysis revealed four distinct groups. The 'High Profile' group had the highest scores in SD and cognitive biases. The 'High Profile' group had higher scores on emotional discomfort. A combination of PLEs and SD may have a potential in early detection of psychosis risk states. Abstract: We aimed to perform a cluster analysis to investigate the group structure of a combination of psychotic-like experiences (PLEs) and self-disturbances in a non-clinical sample. Non-clinical adults ( n  = 677) were assessed with the Community Assessment of Psychic Experiences (CAPE), the Davos Assessment of Cognitive Biases Scale (DACOBS) and the Inventory of Psychotic-Like Anomalous Self-Experiences (IPASE). Cluster analysis was conducted based on the positive and negative dimension of CAPE and a total score of IPASE. Four distinct groups were revealed by the cluster analysis. The High Profile group had the highest means, and the Low Profile had the lowest scores of positive and negative subscales of the CAPE and IPASE. The Positive Profile group had a significantly higher level of self-disturbances (in 'Cognition', 'Consciousnesses and 'Somatization' dimensions) from participants with the 'Negative Profile'. The High Profile group had more cognitive biases (i.e., inadequate cognitive inference about internal and external events) related to psychosis as assessed with DACOBS, had the highest means on each IPASE subscale and had a higher level of emotional distress. A combination of high level of PLEs and self-disturbances may capture the highest risk of psychosis in the general population associated with cognitive biases characteristic for psychosis.